The African writings of self : 1950-2010 : from postcolonial to post-racial ? - (:unkn) unknown (My University, 2014)
We can identify a long autobiographical practice in Africa, if we go back to the Confessions of St. Augustine, and selfwriting has moreover developed in African languages, in pre-colonial and colonial times. At the initiative of anthropologists and Africanists, the first African autobiographies (often written by teachers or students) were collected, while autobiographical writing simultaneously emerged in the French African novel. With the anti-colonial struggle, memoirs were written by leading African politicians, which emphasized the reflexive dimension of African selfwritings. In the postcolonial era, autobiography tends to become more intellectual, oscillating between autobiographical and self-analytic projects. Through a predominantly french-and english speaking corpus, consisting of authors as diverse as Wole Soyinka, Kwame Anthony Appiah, Joseph Emmanuel Nana Appiah, William E. B. Du Bois, Léopold-Sédar Senghor, Lamine Gueye, Amadou Hampâté Bâ, Valentin Yves Mudimbe, Achille Mbembe, Célestin Monga, Barack Obama, Paulin Hountondji or Rasna Warah, our dissertation traces back the mutations of African selfwriting, from the colonial times to the post-colonial era, emphasizing the dialogues established between African authors and French Africanist thinkers, for whom autobiography was much more than a life story. In these literary historical and sociological perspectives, we borrow from Jerome Meizoz his notion of “posture” to study the esthetical, political and literary positions, of various writers and thinkers in African and Western literary fields. We also highlight how self-reflexivity occurs by confronting African self writings to some intellectual autobiographies produced by African-American thinkers and writers. This comparison allows a reflection on the "postcolonial posture" of our authors, and leads to a new problem : the post-racial project that runs through the racialist interpretations of history and identity that characterized
Keywords: African Research